(3cTa GdbfGY Yf hLg CdaGmX TgjI GdSeGYs - (3Ydj Hf eMeO GdeUQj, YdGA GdOjf,J (B1127 (3g` s ((3GHf GdTjN eMehO s)
(3ChdgG (B:s
(3hSejJI HcTa GdbfGY Ydi hLg CdaGX GdSeGY s
(3BNQgG (B:s
(3hCf JdgefG PcQc hJhRYfG TcQc ced GdcJGH s
(3TgjI GdeSGY GdeYQhaI HhUjI GdCOHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B15 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B233s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYGeI HGdQHGW (B- (3GdeZQH (B(360 D) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs